Fractal analysis of Sn-Ag, Sn-Ag-Cu, Sn-Ag-Bi interfacial morphology in flipchip packaging applications - Jayaganthan, R. (2014)
Proceedings of 6th Electronics Packaging Technology Conference, EPTC 2004